(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تُعدّ منطقة الباير البسيط في شمال غرب سوريا، واحدة من السجلات الجيولوجية المميزة والمسجلة بوضوح لعمليات البركنة وعمليات الترسيب ضمن المياه العميقة، على طول الهامش القاري العربي. وتشكل صخور السينيت النيفليني في منطقة قسطل المعاف، لوحا دسريا ضخما شديد التمزق، مغطى بلوح دسري آخر من البيريدوتيت، ينتمي إلى كتلة الباير الاوفيوليتية. وتتألف هذه الصخور تركيبيا من فلزات البلاجيوكلاز و الفلدسبار، وفلزات قلوية تعكس الطبيعة القلوية لهذه الصخور. تدعم نتائج التحاليل الكيميائية هذه الطبيعة، من خلال النسبة العالية لأكسيدي الصوديوم والبوتاسيوم، والاغتناء العالي بعناصر الأثر، التي تؤكد الأصل المعطفي لهذه الصخور. One of the most manifest and distinguished geological record of Mesozoic deep-water sedimentation and volcanism, preserved along the Arabian continental margin, is the Baer–Bassit region, northwestern Syria. Nepheline Syenite rocks in Qastal Maaf form a disrupted thrust sheet, covered by thrust sheet of Peridotite, belongs to ophiolitec Baer block. Compositionally, these rocks consist of plageoclase, feldspre and alkaline minerals and reflects the alkaline nature of these rocks. the chemical analysis supports this nature by presence a high ratio of Na ,K oxides and rare earth elements, which confirm the mantel origin of these rocks.